ANALISIS NILAI WILLINGNESS TO PAY (WTP)ANGKUTAN PENGGUNA ANGKUTAN BECAK MOTOR DI KOTA UJUNG BATU - Bambang Edison (Universitas Pasir Pengaraian, 2011)
In few years later, in town call Ujungbatu, becak motor rising in number because of there is no other transportation service, along with increasing the demand of transport service. But, the becak motor rate determined by the operator, is not consider of the user. That this study analize the Willingness To Pay (WTP) the user of becak motor. Data survey token at Kelurahan Ujungbatu Kota and Kelurahan Suka Damai, in Kecamatan Ujungbatu. With Questioner Home Interview Survey Method. The number of samples based on statistical analysis of the adequacy of the data length parameter in the study area trip. The analys Metode of WTP used perseption approach of becak motor user. From the analysis result, obtained that the interval value of WTP becak motor user about Rp. 3.000,00 – Rp. 4.000,00 per-trip.